Production of methyl ester from oil in the wastewater pond of a palm oil factory - Tongurai, C.; Chuntorng-orn, K. (Songklanakarin Journal of Science and Technology (SJST), 2007)
This research studied the suitable technique for the production of methyl ester from waste palm oil in the water pond of a palm oil mill. The composition of the waste palm oil was 73.82% fatty acid, 5.07% triglyceride, 3.39% diglyceride and 17.76% unknown compounds. The unknown compounds were separated via simple distillation carried out at a temperature range of 300-350oC.First, the experiments were carried out in screw capped bottles using filtrated as-received waste oil as the reactant. The esterification and transesterification process were conducted using sulfuric acid catalyst in a methanol solution. The key parameters studied were mole ratio of waste oil to methanol (1:1 to 1:72), amount of catalyst from 0.1-20 v/w% of the reactant, temperature range of 60-98oC and reaction time range of 15-180 minutes. Thin Layer Chromatography (TLC) analysis showed 85-90% purity of methyl ester with 4-5% of mono-, di-, and triglycerides and fatty acids and about 5-10% of the unknown compounds for the best condition. The resulting yield of biodiesel was 84-88%. Eradication of contaminants by distillation gave about a 75% distillate yield. Distilled waste palm oil was esterified and transesterified using the previous optimum condition of as-received waste oil, but the reaction time and temperature were varied. The optimal result was obtained by using distilled waste palm oil to methanol molar ratio of 1:8, sulfuric acid of 1 v/w% of reactant, reaction temperature of 70oC and reaction time of 1 hour. TLC analysis indicated a biodiesel composition of methyl ester, free fatty acid, diglyceride and monoglyceride of 96.39%, 3.20%, 0.24% and 0.17%, respectively. The yield of biodiesel was 96-98% having physical fuel properties according to Thailand standard for methyl esterFinally, the distilled waste palm oil was esterified using a 3 liters continuous stirred-tank reactor (CSTR). Using the suitable condition for the batch process and an hour retention time, the resulting biodiesel contained methyl ester, free fatty acid, diglyceride and monoglyceride at compositions of 94.34%, 3.22%, 1.60% and 0.84%, respectively, which were very close to the qualities from the batch process.